A expansão da educação superior e a desigualdade regional brasileira: uma análise nos marcos dos planos nacionais de educação - Cristiane de Sousa Brito; André Rodrigues Guimarães (EccoS – Revista Científica)
This article aims to analyze the expansion of higher education in the frameworks of National Education Plans (PNEs), in the perspective of confronting the regional inequality in Brazil. It considers the laws and the documents formulated to orientation of education as important sources of research, in order to reflects policies designed to redress the regional inequalities. The methodology used consists of the bibliographical and documentary research. The results produced informs that the PNEs did not represent solutions to the problem of regional inequality in the expansion of higher education. It concludes that the expansion of this level of education occurs asymmetrically and continues to confirm the social exclusion in the regions North and Northeast of Brazil.